1996
DOI: 10.1177/107110079601700803
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Failed Surgical Management of Fractures of the Base of the Fifth Metatarsal Distal to the Tuberosity: The Jones Fracture

Abstract: Failure of surgical management of fractures of the base of the fifth metatarsal distal to the tuberosity is uncommon. Only one such failure has been reported in the literature to date. The purpose of this article is to present the clinical course of 11 patients with failure of surgically managed jones fractures reviewed by the senior author (J.S.T.). Surgical management was complicated by delayed union in three patients, refracture in seven patients, and nonunion in one patient. The 11 procedures were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(27 citation statements)
references
References 8 publications
0
26
0
1
Order By: Relevance
“…Return to sports should only be allowed when there is radiological evidence of union and the patient is clinically asymptomatic (26). The rehabilitation plan must be accepted by the patient pre-operatively since pre-mature return to vigorous physical activity is believed to cause delayed union and refracture, especially in athletic patients (31). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Return to sports should only be allowed when there is radiological evidence of union and the patient is clinically asymptomatic (26). The rehabilitation plan must be accepted by the patient pre-operatively since pre-mature return to vigorous physical activity is believed to cause delayed union and refracture, especially in athletic patients (31). …”
Section: Resultsmentioning
confidence: 99%
“…Complications of proximal fifth metatarsal fractures include delay union, non-union and refracture (31). A low non-union rate of 0.5% - 1% was reported in zone 1 fractures treated conservatively (20, 33).…”
Section: Resultsmentioning
confidence: 99%
“…Although the current gold standard for treatment is intramedullary screw fixation, delayed unions and refractures with this procedure are not uncommon [5,7,8,11,12]. Bone autografiting could solve the problem because it is osteoconductive, osteoinductive, and provides osteogenic cells [13,14]. …”
Section: Discussionmentioning
confidence: 99%
“…The theoretical advantage of a cannulated screw is the precision and ease if screw placement over a guidewire[25,37]. However, a study done by Glasgow et al[38] reported the risk of re-fracture with cannulated screws. The study examined operative failure of three delayed unions, three nonunions, and five acute Jones fractures.…”
Section: Operative Treatmentmentioning
confidence: 99%
“…They concluded failure was due to undersized cortico-cancellous grafts and incomplete reaming of the medullary canal. Additionally, early return to vigorous physical activity with the bone graft procedure and screw fixation was associated with re-fractures and delayed union[38]. It should be noted that that in this study the definition of Jones fracture included zone two and zone three fractures.…”
Section: Operative Treatmentmentioning
confidence: 99%